Gen Z Digital Leadership through Social Media - Debra Hidayat; Evan Utama Tjandra; Nani Herawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2023)
Born within specific timeframes, typically five to ten years, individuals form distinct generational cohorts that share everyday experiences and traits influenced by the technology that evolves during their formative years. Generation Z, encompassing those born between 1996 and 2006, navigated their childhood, adolescence, and young adulthood with the companionship of smartphones, tablets, social media, online gaming, and various digital interaction platforms. This exploration into Generation Z digital leadership through social media using qualitative methods with netnography and literature review illuminates the dynamic interplay between generational disparities and the evolving digital landscape. New findings underline that if leadership goals and purposes are explicit, Gen Z leaders' disclosures may be perceived as fair by followers, enhancing interaction quality and shaping follower perceptions positively. Social media possesses the potential to bridge gaps, serving as a powerful tool for fostering cohesion and connectivity for Generation Z within a broader range of social contexts. This study found that initiative and high impact are among the main characteristics of Gen Z digital leaders who prefer online over offline discussions. The development and expression of social media consist of personal growth, learning new things, and developing skills and voice. Gen Z digital leaders are found to use social media in various contexts, such as fostering collaboration, building networks, and inspiring action. Gen Z also face challenges while using social media, as they are faced with passivity and communication failure. At the same time, they are blessed with opportunities such as amplifying underrepresented voices, impacting, influencing others, and even inspiring action. Supporting and integrating Gen Z digital leadership skills in practices means knowing the cohort closely, fostering digital literacy in senior generations that work together with them, understanding personal strength, and creating opportunities in the leadership area with safe online environments.